UTILIZAÇÃO DO RESÍDUO DO PROCESSAMENTO DE CAFÉ CONILON NA PRODUÇÃO DE AVICELASES POR Bacillus licheniformis N378 - Freitas, Leonardo da Silva (2020)
The use of bioprocesses allows the production of a large number of metabolites of industrial interest, including microbial enzymes, which can be obtained, even, from the use of agro-industrial residues. The use of these, as a source of substrate, has ensu